Unwired : gaining control over addictive technologies / Gaia Bernstein. - Bernstein, Gaia (Cambridge University Press, 2023)
Our society has a technology problem. Many want to disconnect from screens but can't help themselves. These days we spend more time online than ever. Some turn to self-help-measures to limit their usage, yet repeatedly fail, while parents feel particularly powerless to help their children. Unwired: Gaining Control over Addictive Technologies shows us a way out. Rather than blaming users, the book shatters the illusion that we autonomously choose how to spend our time online. It shifts the moral responsibility and accountability for solutions to corporations. Drawing lessons from the tobacco and food industries, the book demonstrates why government regulation is necessary to curb technology addiction. It describes a grassroots movement already in action across courts and legislative halls. Groundbreaking and urgent, Unwired provides a blueprint to develop this movement for change, to one that will allow us to finally gain control.